#TITLE_ALTERNATIVE# - SETYO MUKTIONO (NIM 25106016), BOBY
This study aims to find a suitable method for determinating priority of individual valuation object to obtain the optimal tax revenue. The study is targeted at obtaining an appropriate criterion and parties to be involved in the process of deciding the priority of individual valuation object. The method used in the study include random method, equal weight method, and pairwise comparison method. The criteria used in the study include Selling Value of Tax Object (SVTO), valuation age, obedience level of taxpayer, and the distance of tax object to tax office. Actors involved in the study were the Head of Valuation and Data Collection Section, the Head of Tax Collecting Section, and Functional Official of Land and Building Tax (LBT) Valuator. Data analysis includes priority order of individual valuation object using pairwise comparison method, priority order of individual valuation object using equal weight method, and priority order of individual valuation object using random method. Analysis results show that priority order using pairwise method potentially increases the Selling Value of Tax Object (SVTO) and gives highest tax payment potention compared to two other methods.